Factor a Quadratic Equation by Grouping

Any quadratic equation with rational roots can be factored by the grouping method. Here are the steps, followed by a few examples.

Steps:

  1. Use algebra to put the equation in standard form with all terms on one side and 0 on the other.
  2. Divide both sides by the greatest common factor (GCF), if any, to get to lowest terms.
  3. Multiply the A coefficient (the squared term) by the C coefficient (the constant), to find AC. Note: "A" and "C" come from Ax2+Bx+C=0, which is the standard form of a quadratic equation.
  4. Find the two integers that multiply together to equal AC and also add together to equal B (the coefficient of the x term).
  5. Rewrite the B term as two new terms using the pair of numbers just found.
  6. Group so that one x term falls into each resultant binomial.
  7. Factor each pair of terms.
  8. Factor again -- you should now have a fully factored expression.
  9. Set each factor equal to zero and solve.
  10. Check your answers.

Example: 4x2-13x=x+30

  1. Subtract x+30 from both sides to get 4x2-14x - 30 = 0.
  2. The GCF is 2, so divide each term by 2. The equation is now 2x2-7x-15=0.
  3. 2 * (-15) = -30, so AC is -30.
  4. The integer pairs that multiply together to equal -30 are: (-1, 30), (-2, 15), (-3, 10), (-5, 6), (1, -30), (-2, 15), (3, -10), and (5, -6)

    We want the pair that adds together to equal -7. Since 3 + (-10) = -7, we choose 3 and -10 as our two numbers.
  5. Rewrite the middle term of our equation using the two numbers just found. The middle term was -7x, so substitute 3x - 10x for the -7x, giving the equation as 2x2 + 3x - 10x - 15=0.
  6. Group to get (2x2+3x)+(-10x-15)=0
  7. Factor each pair of terms: x(2x+3) - 5(2x+3)=0
  8. Factor out the common factor (2x + 3) to get (2x+3)(x-5)=0
  9. Solve each factor
    When 2x + 3 = 0, x = -3/2.
    When x - 5 = 0, x = 5.
    Therefore, x is either -3/2 or 5
  10. Check using the original equation:
    4(-3/2)2 - 13(-3/2) = (-3/2) + 30, so 9 + 39/2 = 57/2, and 57/2 = 57/2. Therefore x = -3/2 is a solution.
    4(5)2 - 13(5) = (5) + 30, so 100 - 65 = 35, and 35 = 35. Therefore x = 5 is a solution and the quadratic has been solved.

Example: x2- 2 = 0

  1. This is already in standard form, although you could write it x2 + 0x - 2 = 0.
  2. The GCF is 1, so no need to divide.
  3. AC = -2
  4. Possible integer pairs are (-1, 2) and (1, -2). Neither pair sums to 0 (our B coefficient), so we now know that x2 - 2 = 0 does not have rational roots.

Result: x2 - 2 = 0 is not factorable in the rational number system. (It can be factored in the reals.)

Example: 6y2 + 11y - 35 = 0

  1. Equation is already in standard form.
  2. Terms are relatively prime (GCF = 1), so no need to divide out common factors.
  3. AC = -210
  4. Possible pairs: (-1, 210), (-2, 105), (-3, 70), (-5, 22), (-6, 35), (-7, 30), (-10, 21) <<< stop here because -10 + 21 = 11, which is what we want!
  5. 6y2 - 10y + 21y - 35 = 0
  6. (6y2 - 10y) + (21y - 35) = 0
  7. 2y(3y - 5) + 7(3y - 5) = 0
  8. (3y - 5)(2y + 7) = 0
  9. 3y - 5 = 0 implies that y = 5/3
    2y + 7 = 0 implies that y = -7/2
    Therefore y is 5/3 or -7/2.
  10. Does 6(5/3)2 + 11(5/3) - 35 = 0? Yes, true.
    Does 6(-7/2)2 + 11(-7/2) - 35 = 0? Yes, true.

Comments

No comments yet.

    Sign in or sign up and post using a HubPages Network account.

    0 of 8192 characters used
    Post Comment

    No HTML is allowed in comments, but URLs will be hyperlinked. Comments are not for promoting your articles or other sites.


    Click to Rate This Article
    working